Adaptation and validation of The Fear of COVID-19 Scale - Faro, Andre (2020)
This work aimed to adapt the Fear of COVID-19 Scale to Brazilian Portuguese, to perform Confirmatory Factor Analysis, to seek evidence of validity based on the relationship with stress and to establish standards for the interpretation of the scale scores. Participated 1,000 adults of both sexes, with an average age of 30.9 (SD = 12.06). The analysis demonstrated that all adjustment indexes were satisfactory, confirming the scale's unidimensionality. The average was 22.2 points (minimum of 7 and maximum of 35 points). Fear of COVID-19 Scale presented convergent validity with the Perceived Stress Scale and strata for the classification of fear intensity in scale were proposed.